Ultimate spy - Melton, H. Keith (Harold Keith), 1944- (DK Pub., 2002)
Learn about famous spies throughout history, how they were recruited, and what really happened during the most daring missions. With more than 700 full-color photos and illustrations, "Ultimate Spy" is the insiderUs guide to the secret world of espionage.